Management of international reserves : the case of Bank of Guyana - Ganga, Gobind ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Presents an overview of the economy and the holdings of international reserves since 1976. Provides an assessment on the level and management of international reserves from the perspective of the various approaches.